2018
DOI: 10.14419/ijet.v7i1.8345
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of 0% infill density surface profile of printed part fabricated by personal FDM 3D printer

Abstract: Fused deposition modeling or FDM technology is an additive manufacturing (AM) technology commonly used for prototyping applications which suffer seriously from low levels of fluctuated surface finish quality, demanding some hand finishing tool for even the necessary levels of 3D printed parts. This paper, therefore, aims at giving close attention to the variation in the surface roughness profile between the inner and the outer faces of FDM 3D printed parts based on advanced polylactic acid (PLA+) thermoplastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Fused deposition modeling (FDM, developed in the 1980s [6] and commercialized in 1990 [7]) is additive manufacturing (AM) technologies that build automatically three-dimensional (3D) physical parts by heating up and extruding down the thermoplastic filaments materials through a small nozzle, without any tooling or machining [8,9,10] and also by eliminating the need for human interventions [11]. They are not only used to fabricate prototypes, but final products are also manufactured with these types of machines [12] with a dimensional tolerance equal to ±1 mm overall [13].…”
Section: Introductionmentioning
confidence: 99%
“…Fused deposition modeling (FDM, developed in the 1980s [6] and commercialized in 1990 [7]) is additive manufacturing (AM) technologies that build automatically three-dimensional (3D) physical parts by heating up and extruding down the thermoplastic filaments materials through a small nozzle, without any tooling or machining [8,9,10] and also by eliminating the need for human interventions [11]. They are not only used to fabricate prototypes, but final products are also manufactured with these types of machines [12] with a dimensional tolerance equal to ±1 mm overall [13].…”
Section: Introductionmentioning
confidence: 99%
“…The traces were auto-leveled, set up to a linear least-squares (LLS) straight line and then filtered with a standard lowpass of 0.8 mm cut-off wavelength and filter CR ISO. Details of the average surface roughness measurements procedure and calibration trials have been reported elsewhere [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. In general, the calibration results showed that the cantilever beam system (stylus with beam) at only one end was a linear mass-spring system (R 2 > 0.999) under operational and environmental conditions, generally at 20°C ± 1°C temperature and 40% ± 5% relative humidity, with an absolute uncertainties value of < 1% and measurement resolution down to at worst 50 nm.…”
Section: Measuring Methodsmentioning
confidence: 99%
“…The traces were auto-leveled direction and set-up to a linear least-squares (LLS) fitting technique (single scan mode) and after that is filtered with a standard low-pass filter (LPF) of 0.8 mm effective cut-off wavelength. Full details of the measurement procedure have been reported elsewhere [18][19][20][21][22]. The calibration results using a standard ball of 22.0161 mm diameter (from Taylor Hobson Precision, Ltd.) after a series of trials showed that the system of the one-end cantilever beam was a linear massspring system regression of R 2 > 0.99, under various working and eco-friendly issues, with an absolute value of each uncertainty of <1% and displacement measurement resolution down to at worst performance of 50 nm.…”
Section: Surface Roughness Profile Inspectionmentioning
confidence: 99%
“…Main AM systems are fused deposition molding (FDM) [13], stereolithography (SL) [14], laminated object manufacturing (LOM) [15], selective laser sintering (SLS) [16] and laser engineered net shaping (LENS) [17]. One of the most widely used technologies for 3D printing compared to others competing for dimensional printing technologies is fused deposition modeling (FDM) [18,19,20,21,22] and it is this which is predicted as a sustainable modern manufacturing platform for functional and structural products and also for industrial and house-use [23].…”
Section: Introductionmentioning
confidence: 99%